Where Infants Go: Real‐Time Dynamics of Locomotor Exploration in Crawling and Walking Infants. Issue 3 (5th June 2019) - Hoch, Justine E.; Rachwani, Jaya; Adolph, Karen E.
Abstract : Where do infants go? A longstanding assumption is that infants primarily crawl or walk to reach destinations viewed while stationary. However, many bouts of spontaneous locomotion do not end at new people, places, or things. Study 1 showed that half of 10‐ and 13‐month‐old crawlers' ( N  = 29) bouts end at destinations—more than previously found with walkers. Study 2 confirmed that, although infants do not commonly go to destinations, 12‐month‐old crawlers go to proportionally more destinations than age‐matched walkers ( N  = 16). Head‐mounted eye tracking revealed that crawlers and walkers mostly take steps in place while fixating something within reach. When infants do go to a destination, they take straight, short paths to a target fixated while stationary.